PENGUATAN KARAKTER TANGGUNG JAWAB SEBAGAI UPAYA PENINGKATAN MUTU INDIVIDU DI ERA DIGITAL - Awla Putri Adibah; Sutrisno Sutrisno; Suwadi Suwadi (Jurnal Manajemen Pendidikan, 2026)
The development of globalization and digitalization has a significant impact on the formation of individual character in modern life. Technological advances not only bring positive impacts, but also give rise to various problems such as a decreased sense of responsibility, low discipline, and increased individualistic behavior. This study aims to analyze the strengthening of the character of responsibility as an effort to improve the quality of life of individuals. The method used in this study is a library study (library research) with a qualitative descriptive approach through the review of various literature sources in the form of books, journals, scientific articles, and other relevant sources. The results of the study indicate that the character of responsibility plays a significant role in shaping individual quality, both in moral, social, emotional, and professional aspects. The formation of the character of responsibility takes place through a process of habituation in the family, educational, and community environments. In addition, the digital era presents challenges in strengthening character due to low social control and the increasing use of technology unwisely. Therefore, strengthening the character of responsibility needs to be done continuously through habituation, role models, and synergy between families, educational institutions, and the community to create individuals who are qualified, have integrity, and are adaptive to the times.